PENGARUH MUSIK AMERIKA LATIN TERHADAP INDONESIA - Cabrera, Daniel Antonio Milan (Institut Seni Indonesia (ISI) Surakarta, 2020)
Since the beginning of the last century, Latin American music has been succes in the U.S. music industry because its intrinsic musical characteristics and its involvement within the film industry. Through the U.S. and Europe, it has been influencing popular music around the world; including Indonesia, Malaysia, Singapore, and India, countries that also contributed to the diffusion of Latin styles in Indonesia. The corpus of original works of Indonesian-Latin music is quite huge and has great quality; particularly audio recordings done in the 1950s and 1960s that mixed Latin, Western, and regional musical elements to create new musical forms know as lagu daerah (regional songs) and pop daerah (regional pop). This article aims to provide some understandings of this complex diffusion process utilising mainly a bibliographical research method (books, journals, digital news, etc.), interviews, and listening-based information from old audio recordings. My hipothesis is that Latin American music has been well accepted in Indonesia, espetially in Java and Sumatra, due to historical crossroads that spread musical and cultural similarities in both regions. In order of its importance in Indonesian-Latin music, these are: the conection of Asia and America during the Spanish, Portugal, and Holand colonial era; the Islamic influence in Indonesia, India, Malaysia, and the Iberic peninsula; the influence of Dutch music in Indonesia and German music in Latin America; the role of African music in Latin America and the probable two side influences between Africa and Indonesia; and the inmigration to Amerika from Nusantara-Oceania sailors in prehistoric times.